1993
DOI: 10.1115/1.2929488
|View full text |Cite
|
Sign up to set email alerts
|

On the Collapse of Long, Thick-Walled Tubes Under External Pressure and Axial Tension

Abstract: The paper presents the results from a combined experimental and analytic study on the collapse of long, thick-walled tubes subjected to external pressure and axial tension. The experiments involved tubes of diameter-to-thickness ratio (Dm/t) 10 to 40. Collapse envelopes were obtained for two different pressure-tension loading paths. Collapse tests involving initially ovalized tubes were also carried out. The collapse strength predicted with a two-dimensional elasto-plastic model applying J2 flow rule was in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The results were validated through comparison with a series of experimental data obtained and presented by Madhavan [14].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results were validated through comparison with a series of experimental data obtained and presented by Madhavan [14].…”
Section: Introductionmentioning
confidence: 90%
“…The finite element analysis method proposed in this paper was validated by comparing against experimental data corresponding to steel casings used commercially and presented by Madhavan [14]. The seamless, cold drawn, 304 stainless steel casings which are manufactured according to the API Specification 5LX standards were used for comparison purposes in this study.…”
Section: Model Validationmentioning
confidence: 99%
“…Thick-walled tubular specimens are used to replicate real-life structures such as bridge girders [66], high pressure containers, and deep submersibles in power plants or even as protective oil casing conduits in oil and natural gas extraction [67]. On the other hand, thin-walled test pieces appear to be suitable for simulating the loading that could be experienced by shell structures such as a pressure vessel or piping [63], a bicycle frame or even an aircraft wing [68].…”
Section: Cylindrical Solid and Tubular Biaxial Fatigue Specimensmentioning
confidence: 99%
“…Later, Madhavan et al. 131 extended their study to pipes with D/t ratios ranging from 10 to 40. They found that the extent of the reduction in the collapse pressure of the pipe and the nature of the collapse pressure-tension interaction profile are strongly dependent on the stress–strain behaviour of the pipe’s material.…”
Section: Analysis Of Offshore Pipes Under Different Loadsmentioning
confidence: 99%